Decoding “Asap-Asap itu Telah Menghilang”: Understanding Environmental Crisis in Indonesia’s Short Story - Sofyaningrum, Rosita (Lingual Journal of Language and Culture, 2024)
Abstract This research focuses on the analysis of language and narrative in understanding how literary works can contribute to public awareness and understanding of the environmental crisis in Indonesia. It serves as an initial step in comprehending the role of language and literature in depicting the environmental crisis in the country. The study aims to reveal how the use of language, narrative, characters, symbolism, environmental context analysis, and environmental crisis analysis in the short story "The Vanishing Smoke" can provide a deeper understanding of the environmental crisis in Indonesia. The research method employed is an in-depth text analysis to comprehend the short story "The Vanishing Smoke." The methodology includes data collection, text analysis, and contextual analysis. The findings include: (1) Language analysis consisting of diction, language style, symbolism, and elements in the short story. (2) Environmental Context Analysis, including environmental context and environmental crisis. (3) Environmental Crisis Analysis, encompassing the messages in the short story, the environmental issue perspective in depicting the main character's feelings, and the implied messages to the public regarding environmental issues.   Keywords: Indonesia’s Short Story, Environmental Crisis